Sistem Pendukung Keputusan Cerdas untuk Pemilihan Jenis Tanaman Pertanian Kota - Ramadhan, Jeri; Hermadi, Irman; Sitanggang, Imas Sukaesih (Jurnal Pendidikan Informatika (EDUMATIC), 2024)
Urban farming activities have become increasingly popular to meet their food needs in urban areas. Jakarta as provinces with a population density of high, have a program of urban farming is developed by the farmers to urban Balkot Farm. This study aims to support system to develop a clever move the crop farm a town with the simple additive weighting (SAW). The methods used to obtain the highest related alternative plant assessed according to its parameters that affect the eligibility of land and a room with a variety of plants. The methodology used software development life cycle (SDLC) prototyping model consisting of five of the communication, quick plan, modeling quick design, construction of prototype deployment and delivery and feedback. Data collection method using interviews and the study of literature. Research results of a web application system that has an alternative menu, criteria, subcriteria, rating match and results. Smart decision support system based on black box testing and user acceptance testing successfully shows menus according to land criteria that will be used according to stakeholder needs.